METODA PEMBUATAN ADONAN UNTUK MENINGKATKAN MUTU ROTI MANIS BERBASIS TEPUNG KOMPOSIT YANG DIFORTIFIKASI RUMPUT LAUT - . Kartiwan; Zulianatul Hidayah; Bachtaruddin Badewi (Partner, 2008)
Dough Methods for Improving Quality of Sweet Bread On Composite Flour Bases. The experiment was conducted at Food Technology Laboratory Politani Negeri Kupang from April to November 2007. The experiment used RCBD. The factors consisted of Composite Flour (0%, 10%, 20%, 30%) and The Methods of Dough (Straight Dough, Sponge Dough, and Dough Break Roll/DBR), and 3 replications. The variables observed were volume expansion, porosity, texture, moisture, crude fiber bread and total (colony) microorganisms. Data were analyzed using Analysis of Variance and Duncan Multiple Range Test. Addition of composite flour to dough until 30% affected on characteristics of bread: expansion was lower, the total porosity that medium-large size lower, texture more hard, crude fiber higher, the total microbe colony lower. The Straight Dough produced bread that expansion was normal, texture soft, and the total microbe colony higher. The Sponge Dough produced bread that expansion was medium, texture rather soft, crude fiber and total microbe colony lower. The Dough Break Roll (DBR) produced bread that expansion was highest, porosity medium and texture soft, crude fiber high, total microbe colony low. The best methods for sweet bread were Dough Break Roll method (DBR) and the best composition was composite flour 10%. Keywords: composite flours, dough methods, sweet bread